Population ecology of two woodland caribou herds in the southern Yukon - Farnell, Richard; Barichello, Norman; Egli, Katherina; Kuzyk, Gerry (Rangifer, 1996)
Since the mid 1980's, the Aishihik herd of woodland caribou (Rangifer tarandus caribou) declined from approximately 1500 to 583 animals. During the same period a nearby herd, the Wolf Lake Herd increased from approximately 664 to 1249 animals. This paper compares aspects of the ecology of these two herds to determine how these relationships conform to a general model of caribou population ecology described by Seip (1992). Comparisons include caribou demographic characteristics and distribution patterns, predator densities, abundance of alternate prey, human hunting and snow depth on caribou winter range. Ecological differences between herds were apparent in the ratio of prime bulls to cows, the abundance of moose (Alces alces), the occurrence of coyotes (Canis latrans), late winter snow conditions, and access to hunting. We hypothesize that the Wolf Lake herd was able to grow because wolves Canis lupus) preyed mainly on the relatively abundant moose population. A highly clumped winter caribou distribution may have further reduced the impact of wolf predation on the Wolf Lake herd. In contrast, the decline of the Aishihik herd was accompanied by a relative scarcity of moose, few prime aged caribou bulls probably due to a more liberal trophy harvest, and wider late-winter dispersion that offered wolves greater access to caribou. The decline may have been exaggerated by the peak in the snowshoe hare (Lepus americanus) cycle which may have temporarily improved wolf pup survival. We suspect that moose are normally the primary prey of wolves in the Yukon and that a decline in moose eventually results in their being too scarce to offer an economical prey choice, prompting a prey switch to caribou. Results of our analyses conform incompletely to Seip's (1992) model for woodland caribou population ecology, particularly because the Wolf Lake herd prospered where moose were relatively abundant.